An Approach to Argumentative Reasoning Servers with Multiple Preference Criteria - Teze, Juan Carlos (2013)
Argumentation is an attractive reasoning mechanism due to its dialectical and non monotonic nature, and its properties of computational tractability. In dynamic domains where the agents deal with incomplete and contradictory information, to determine the accepted or warranted information, an argument comparison criterion must be used. Argumentation systems that use a single argument comparison criterion have been widely studied in the literature. In some of these approaches, the comparison is xed and in others the criterion can be replaced in a modular way. In this work we introduce an argumentative server that provides recommendations to its client agents and the ability to decide how multiple argument comparison criteria can be combined. In the proposed formalism, the argumentative reasoning is based on the criteria selected by the client agents. As a result, a set of operators to combine multiple preference criteria is presented.